PERLINDUNGAN HUKUM TERHADAP FRANCHISOR DAN FRANCHISEE PADA USAHA WARALABA DALAM PERSPEKTIF HAK KEKAYAAN INTELEKTUAL (Studi Aspek Hukum Perjanjian) - Arif Effendi (Sekolah Tinggi Pariwisata Mataram, 2021)
The expansion of business has passed the limit of space, time and territory of a country. One of efforts in entering others country to expand business is by using franchise system. That’s why so many entrepreneur starting their business not by establishing the new one, but by purchasing business system called franchise. In Indonesia the word of franchise known as waralaba and regulated by the regulation of the government of Republic of Indonesia Number 42 Year 2007 upon Franchise. Literally waralaba can be interpretedas a business which is giving more profit. In short,a franchise is the agreement between two legally independent parties which gives : First, a person or group of people (franchisee) the right to market the product or service using the trademark of another business (franchisor). Second,the franchisee the right to market a product or service using the operating method offranchisor.Third, the franchisee the obligation to pay the franchisor fees for this right. Forth,the franchisor the obligation to provide the rights and suport to franchisee. The agreement made between the franchisor and the franchisee on franchise must have legal protection in it, in particular with regard to the use of Intellectual Property Rights. The agreement has to cover law protection relates to the rights and obligations of both franchisor and franchisee, so that during the agreement both parties adhere to each other. For that it takes a good agreement and benefiting both parties.